2021
DOI: 10.1136/heartjnl-2021-319760
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes among adult survivors of total cavopulmonary Fontan palliation for single ventricle

Abstract: ObjectiveThis tertiary centre study aims to identify factors associated with adverse outcomes in adult survivors with total cavopulmonary connection (TCPC) Fontan palliation for single ventricle.MethodsThis retrospective review of medical records identified adult (≥18 years) survivors of TCPC Fontan palliation who were followed at a single tertiary centre between 1 January 2000 and 1 July 2019. Adverse outcomes were defined as arrhythmia, pacemaker/implantable cardioverter defibrillator placement, liver cirrho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Moreover, it was reported that adverse outcome-free survival rates 10, 20, and 25 years post-TCPC were 89%, 60%, and 24%, respectively. Additionally, extracardiac TCPC was identified as an independent risk factor for adverse outcomes in a multivariate model [ 14 ]. Risk factors affecting long- and short-term outcomes after TCPC include, but are not limited to, the timing of TCPC operation [ 15 ], flow dynamics of bilateral superior cavopulmonary shunts [ 16 ], older age at stage-2 palliation [ 17 ], and systemic to pulmonary collateral blood flow [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was reported that adverse outcome-free survival rates 10, 20, and 25 years post-TCPC were 89%, 60%, and 24%, respectively. Additionally, extracardiac TCPC was identified as an independent risk factor for adverse outcomes in a multivariate model [ 14 ]. Risk factors affecting long- and short-term outcomes after TCPC include, but are not limited to, the timing of TCPC operation [ 15 ], flow dynamics of bilateral superior cavopulmonary shunts [ 16 ], older age at stage-2 palliation [ 17 ], and systemic to pulmonary collateral blood flow [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 Prior studies have identified various long‐term sequelae of the Fontan procedure, including arrythmias, heart failure (HF), thromboembolic events, cirrhosis, protein‐losing enteropathy, and death. 6 , 7 , 8 , 9 , 10 Researchers have previously identified several risk factors associated with these adverse cardiovascular events. However, these factors are mainly nonmodifiable, including preoperative conditions, type of operation, and timing of the procedure.…”
mentioning
confidence: 99%
“…Over the last 50 years, the Fontan procedure has become a mainstay for children born with a single functional ventricle. However, several disputes persist: What is the best configuration for total cavo-pulmonary connection (TCPC), lateral tunnel vs. extracardiac connection [7]? How best to prevent Fontan failure?…”
mentioning
confidence: 99%